Implantable cardioverter defibrillator therapy in repaired tetralogy of Fallot after pulmonary valve replacement: Implications for the mechanism of ventricular arrhythmia. (15th December 2017) - Chiu, Shuenn-Nan; Huang, Shu-Chien; Wang, Jou-Kou; Lu, Chun-Wei; Chang, Ling-Yin; Lin, Ming-Tai; Chen, Chun-An; Chen, Yih-Sharng; Wu, Mei-Hwan
Abstract: Background: Ventricular tachycardia (VT), which is related to haemodynamic and electrophysiological alterations, is an important complication in repaired tetralogy of Fallot (rTOF) patients. We defined the role of implantable cardioverter defibrillator (ICD) therapy after pulmonary valve replacement (PVR) and the implications of coexisting long QT gene mutations/polymorphisms. Methods: From 2003 to 2016, rTOF patients with VT who received ICD implantation were enrolled. rTOF patients without VT served as a control group. We performed long QT gene mutation analysis through the direct sequencing method. Results: In total, 12 (male/female, 8/4) patients with VT received ICD implantation. The mean age at TOF repair and ICD implantation was 4.4 ± 4.5 years and 27.1 ± 11.5 years, respectively. All but one patient received PVR for severe pulmonary regurgitation or repair for a residual ventricular septal defect. After 5.4 ± 4.0 years of follow-up, six patients (50%) had at least one episode of appropriate shock: two had received PVR with intraoperative arrhythmia ablation and two had received PVR only. Compared with 121 patients without VT, the ICD patients had a higher frequency of long QT gene mutation/polymorphisms (10/12 vs. 54/121, p  = 0.014), especially in the hERG and SCN5A genes. The mechanism of VT in rTOF was discussed thoroughly. Conclusion: In rTOF patients who received ICD as secondary prevention, the appropriate shock rate remained high despite PVR and intraoperative arrhythmia ablation. Coexisting long QT gene mutations/polymorphisms may be associated with ventricular arrhythmia.